Cost-Effectiveness Analysis of Biomarker-Guided Treatment for Metastatic Gastric Cancer in the Second-Line Setting. (17th February 2020) - Lauren, Brianna; Ostvar, Sassan; Silver, Elisabeth; Ingram, Myles; Oh, Aaron; Kumble, Lindsay; Laszkowska, Monika; Chu, Jacqueline N.; Hershman, Dawn L.; Manji, Gulam; Neugut, Alfred I.; Hur, Chin
Abstract : Background . The 5-year survival rate of patients with metastatic gastric cancer (GC) is only 5%. However, trials have demonstrated promising antitumor activity for targeted therapies/immunotherapies among chemorefractory metastatic GC patients. Pembrolizumab has shown particular efficacy among patients with programmed death ligand-1 (PD-L1) expression and high microsatellite instability (MSI-H). The aim of this study was to assess the effectiveness and cost-effectiveness of biomarker-guided second-line GC treatment. Methods . We constructed a Markov decision-analytic model using clinical trial data. Our model compared pembrolizumab monotherapy and ramucirumab/paclitaxel combination therapy for all patients and pembrolizumab for patients based on MSI status or PD-L1 expression. Paclitaxel monotherapy and best supportive care for all patients were additional comparators. Costs of drugs, treatment administration, follow-up, and management of adverse events were estimated from a US payer perspective. The primary outcomes were quality-adjusted life years (QALYs) and incremental cost-effectiveness ratios (ICERs) with a willingness-to-pay threshold of $100, 000/QALY over 60 months. Secondary outcomes were unadjusted life years (survival) and costs. Deterministic and probabilistic sensitivity analyses were performed to evaluate model uncertainty. Results . The most effective strategy was pembrolizumab for MSI-H patients and ramucirumab/paclitaxel for all other patients, adding 3.8 months or 2.0 quality-adjusted months compared to paclitaxel. However, this strategy resulted in a prohibitively high ICER of $1, 074, 620/QALY. The only cost-effective strategy was paclitaxel monotherapy for all patients, with an ICER of $53, 705/QALY. Conclusion . Biomarker-based treatments with targeted therapies/immunotherapies for second-line metastatic GC patients substantially improve unadjusted and quality-adjusted survival but are not cost-effective at current drug prices.